The role of SARS-CoV-2 infection in patients with bronchial asthma and allergic rhinitis at tertiary St. George Hospital Plovdiv, Bulgaria - Dermendzhiev, Svetlan; Petrova, Atanaska; Lengerova, Gergana; Dimitrova, Nikoleta; Deleva, Petya (The Journal of Infection in Developing Countries, 2026)
Introduction: The COVID-19 pandemic has generated uncertainty about epidemiology, clinical course, and the influence of comorbidities. Evidence is conflicting on whether bronchial asthma and allergic rhinitis alter susceptibility to SARS‑CoV‑2 or the severity of COVID‑19. This study describes occurrence and clinical course of SARS‑CoV‑2 infection in a small cohort of patients with allergic respiratory comorbidities. Methodology: Nineteen patients with PCR‑confirmed COVID‑19 were observed from 11 to 30 November 2020 at the Department of Occupational Diseases with Clinical Allergy Activity, University Hospital “St. George”, Plovdiv. Viral RNA was extracted from respiratory specimens using automated systems and amplified by real‑time PCR; cycle threshold (Ct) values were recorded as an indirect viral load measure. The department was temporarily reorganized as a dedicated COVID‑19 unit and care followed institutional protocols based on international evidence. Data were obtained retrospectively from official medical records; informed consent was included. Results: Clinical histories, examinations, and laboratory data were reviewed for all 19 patients. Six had bronchial asthma and three had allergic rhinitis. Although the sample is small and not statistically representative, allergic respiratory diseases were observed to coexist with SARS‑CoV‑2 infection in this hospitalized series. Conclusions: Given the lung’s central role in both allergic airway disease and COVID‑19, clinicians should evaluate infection risk and clinical implications in patients with asthma and allergic rhinitis to inform prevention and management strategies.